Training of Future Primary School Teachers for the Use of Audio-Visual Teaching Aids - Kuzio, Ihor (Pedagogical Discourse, 2011)
On the basis of the analysis of psychological and educational literature the main issues of training of future primary school teachers to the use of audio-visual means of training in their work are elucidated in the article, the key issues that arise in the process of teaching students are examined.